2021
DOI: 10.3390/molecules26072036
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological Activity and Survival Rate of Rats Nervous Tissue Cells Depends on D/H Isotopic Composition of Medium

Abstract: The deuterium content modification in an organism has a neuroprotective effect during the hypoxia model, affecting anxiety, memory and stress resistance. The aim of this work was to elucidate the possible mechanisms of the medium D/H composition modification on nerve cells. We studied the effect of an incubation medium with a 50 ppm deuterium content compared to a medium with 150 ppm on: (1) the activity of Wistar rats’ hippocampus CA1 field neurons, (2) the level of cultured cerebellar neuron death during glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The brain is the most sensitive organ to the disturbance of redox homeostasis [4][5][6][7]. This is due to the following factors.…”
Section: Introductionmentioning
confidence: 99%
“…The brain is the most sensitive organ to the disturbance of redox homeostasis [4][5][6][7]. This is due to the following factors.…”
Section: Introductionmentioning
confidence: 99%
“…For decades, various efforts have been made to explore the biology isotope effects of biogenic elements. Despite the increasing knowledge of the biological isotope effect, a comprehensive understanding of the effects in the biological context has not yet been achieved (2,(5)(6)(7)(8)(9). Among the main biogenic elements (C, H, O and N), deuterium has been investigated in a number of studies and its effects on organisms have been demonstrated (5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the increasing knowledge of the biological isotope effect, a comprehensive understanding of the effects in the biological context has not yet been achieved (2,(5)(6)(7)(8)(9). Among the main biogenic elements (C, H, O and N), deuterium has been investigated in a number of studies and its effects on organisms have been demonstrated (5)(6)(7)(8)(9). However, the carbon isotope effects of bioactive compounds have yet not been investigated, at least to the best of our knowledge, although such studies are important to the biology development in theory and application.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, even relatively small increases or decreases in its concentration affect physiological processes at all levels: molecular, cellular, tissue, organ and organism [ 6 , 7 , 8 , 9 , 10 ]. Many studies have shown that a decrease in the deuterium content supports the body’s defense systems, including nonspecific mechanisms [ 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%